2018
DOI: 10.1002/lary.27559
|View full text |Cite
|
Sign up to set email alerts
|

Children with unilateral cochlear nerve canal stenosis have bilateral cochleovestibular anomalies

Abstract: Objectives/Hypothesis To investigate the cochleovestibular apparatus bilaterally in children with isolated unilateral bony cochlear nerve canal (bCNC) stenosis. Study Design Retrospective review. Methods Imaging studies of children with unilateral bCNC stenosis (<1.0 mm) on computed tomography imaging (N = 36) were compared with controls imaged due to trauma without temporal bone injury (N = 32). Twenty‐six measurements were obtained in each ear, assessing the bony internal auditory canal (IAC), cochlea, and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…A previous study described a wider cochlear basal turn lumen and abnormal lateral SCC bony island in the contralateral normal hearing ears of children with unilateral hearing loss, compared with controls . Similarly, a higher rate of contralateral cochleovestibular anomalies was reported in children with unilateral hearing loss and cochlear nerve canal stenosis, compared with controls . The authors proposed a role for abnormal signaling during embryogenesis that affects the temporal bones bilaterally, yet the clinical significance of these findings is to be elucidated.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…A previous study described a wider cochlear basal turn lumen and abnormal lateral SCC bony island in the contralateral normal hearing ears of children with unilateral hearing loss, compared with controls . Similarly, a higher rate of contralateral cochleovestibular anomalies was reported in children with unilateral hearing loss and cochlear nerve canal stenosis, compared with controls . The authors proposed a role for abnormal signaling during embryogenesis that affects the temporal bones bilaterally, yet the clinical significance of these findings is to be elucidated.…”
Section: Discussionmentioning
confidence: 94%
“…15 Similarly, a higher rate of contralateral cochleovestibular anomalies was reported in children with unilateral hearing loss and cochlear nerve canal stenosis, compared with controls. 16 The authors proposed a role for abnormal signaling during embryogenesis that affects the temporal bones bilaterally, yet the clinical significance of these findings is to be elucidated. A previous study by the senior author showed that 10.6% of 142 children with unilateral hearing loss later developed contralateral hearing loss, similar to the 15% rate of bilateral findings we observed in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Even this study did not include MR images nor a normal control group. Vilchez-Madrigal et al 42 compared the CT imaging studies of 36 children with unilateral CA stenosis (< 1.0 mm), with controls without temporal bone injury. Contralateral ears had smaller CA ( p < 0.00) and cochlea ( p < 0.00) than controls, although to a lesser extent than on the stenotic side.…”
Section: Discussionmentioning
confidence: 99%
“…A narrow IAC is found more often in children with SNHL compared with children without SNHL 9,18,20 . IAC stenosis should be an absolute contraindication to cochlear implantation.…”
Section: Discussionmentioning
confidence: 93%